0.43 THz emission from high-Tc superconducting emitters optimized at 77 K. (11th December 2015) - Minami, H; Watanabe, C; Kashiwagi, T; Yamamoto, T; Kadowaki, K; Klemm, R A
Abstract: A liquid helium-free, compact and continuous sub-terahertz radiation system operating at 77 K has been developed using a rectangular mesa device made from a high -superconducting Bi2 Sr2 CaCu2 O single crystal, based on a different design of a stand-alone mesa sandwich structure to reduce the dc-current Joule heating effects. The mesa was thermally connected to sapphire plates through thin thermal grease embedded with diamond nano-crystals. When immersed in liquid N 2, the device emits intense radiation at 0.437 THz, the highest frequency ever achieved at 77 K, due to excitation of the TM(1, 0) rectangular cavity mode. By varying the dc current–voltage bias and the bath temperature in a He-flow cryostat, the device's emission frequency is broadly tunable from 0.31 THz at 79 K to 1.31 THz at 30 K.